SOIL FERTILITY STATUS IN MANDALA COSTUMARY FOREST BASED ON TOPOGRAPHY LEVELS - Tuti Mutia; Sumarmi Sumarmi; Ravines Rohit Prasad (Universitas Muhammadiyah Mataram, 2023)
Abstract: The level of soil fertility based on nutrients is influenced by the topography of a region. The purpose of this study was to determine the status of soil fertility at a topography of 300-350 masl in the Mandala customary forest based on C, N, P and K content. , 320-330 masl, 330-340 masl and 340-350 masl. Soil analysis uses chemical laboratory tests to determine the content of C, N, P and K. Elements C, N, P and K are associated with soil fertility criteria. Then determining the status of soil fertility is done by looking for the scoring of the element criteria. The results showed that the status of soil fertility in the Mandala customary forest was very high. At 330-350 masl topography, soil fertility is classified as very high, while soil fertility is very high at 300-330 masl topography. The higher a place, the chemical properties of the soil will increase, so that soil fertility will increase. The altitude limit that affects soil fertility starts from 0 masl <-> 3000 masl. Soil fertility status can be used as a guide in making decisions in managing forests to maintain the availability of nutrients.Abstrak:Tingkat kesuburan tanah berdasarkan unsur hara dipengaruhi oleh topography suatu wialyah. Tujuan penelitian ini adalah untuk mengetahui status kesuburan tanah pada topografi 300-350 mdpl di hutan adat Mandala berdasarkan kandungan C, N, P dan K. Sampel tanah diambil dari 5 titik topografi yang berbeda yaitu pada ketinggian 300-310 mdpl, 310-320 mdpl, 320-330 mdpl, 330-340 mdpl dan 340-350 mdpl. Analisis tanah menggunakan uji laboratorium kimia untuk mengetahui kandungan C, N, P dan K. Unsur C, N, P dan K dikaitkan dengan kriteria kesuburan tanah. Kemudian penentuan status kesuburan tanah dilakukan dengan mencari skoring dari kriteria elemen. Hasil penelitian menunjukkan bahwa status kesuburan tanah di hutan adat Mandala sangat tinggi. Pada topografi 330-350 mdpl, kesuburan tanah tergolong sangat tinggi, sedangkan kesuburan tanah sangat tinggi pada topografi 300-330 mdpl. Semakin tinggi suatu tempat maka sifat kimiawi tanah semakin meningkat, pada ketinggian sehingga kesuburan tanah semakin meningkat. Batas ketinggian yang mempengaruhi kesuburan tanah mulai dari 0mdpl<->3000mdpl. Status kesuburan tanah dapat dijadikan pedoman dalam mengambil keputusan dalam mengelola hutan untuk menjaga ketersediaan unsur hara.